Disentangling the identity of the genus Biatorellina (Leotiomycetes, Ascomycota) - Quijada, Luis; Polhorský, Adam; Mitchell, James K.; Pfister, Donald H. (Phytotaxa, 2019)
The monotypic genus Biatorellina is currently considered a taxonomic synonym of Tryblidiopsis but has an obscure and complicated history. During the revision of the genus Tympanis a syntype of Biatorellina buchsii was fortuitously found and reviewed. Initially our revision led to the hypothesis that B. buchsii could be conspecific with Tympanis confusa. A bibliographic and morphological revision, together with a biometric study, was done using the syntype of B. buchsii and specimens of Tympanis confusa to verify the identity of the genus Biatorellina. Our results show an overlap in the morphology, biometry, distribution and ecology of B. buchsii (≡ Tympanis buchsii) and Tympanis confusa. The identity and the placement of Biatorellina is resolved and B. buchsii is proposed as a synonym of Tympanis confusa.